A Study on Effectiveness of Celebrity Marketing on Boosting Customer Endearment in Kerala - Sreenivasan, Sruthi (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Celebrity marketing is a commonly used method to attract customers or consumers to the market. It is a tactic to foster consumer needs by channelizing their dedication and likeliness towards celebrities like film stars, sports players and all other well- known personalities. This study focuses on the effectiveness of such tactic to increase the customer preferences.